Liver iron concentration and distribution in chronic hepatitis C before and after interferon treatment. Issue 1 (July 1997) - Boucher, E; Bourienne, A; Adams, P; Turlin, B; Brissot, P; Deugnier, Y
Abstract : BACKGROUND: Recent studies have suggested that, in patients with chronic hepatitis C, elevated iron stores are predictive of a poor response to interferon. AIMS: To assess liver iron concentration and distribution before and after interferon treatment in patients with hepatitis C in order to evaluate further the role of iron in the pathogenesis of hepatitis C. PATIENTS: Fifty-five patients with hepatitis C treated with alpha interferon for six months. METHODS: Patients were evaluated for liver iron concentration (normal value < 36 mumol/g), and liver iron distribution before and six months after therapy. RESULTS: At entry: liver iron concentration was elevated in 16/55 patients (29%); iron staining (Perls' staining) was found in 31/55 patients (56%) mainly within Kupffer and endothelial cells. Iron load was significantly higher in patients with the most histological inflammatory activity. Following treatment: liver iron concentration decreased significantly (40 (24) to 30 (17) mumol/g, p = 0.001); this was related to iron depletion in mesenchymal cells. Iron depletion occurred regardless of the response to therapy. Elevated liver iron concentration was not found to be a predictive factor of failure of interferon. CONCLUSION: Although liver iron stores were usually normal or only slightly elevated in patients with chronic hepatitis C, biochemical and histological liver iron content decreased following treatment due to the diminution in mesenchymal iron deposits. Iron depletion was interpreted as both a consequence of the anti-inflammatory effect of treatment and a factor of improvement in liver histology.